The role of social capital in facilitating hepatitis C treatment scale‐up within a treatment‐as‐prevention trial in the male prison setting. (18th October 2020) - Lafferty, Lise; Rance, Jake; Dore, Gregory J.; Lloyd, Andrew R.; Treloar, Carla
Abstract: Background and Aims: Hepatitis C (HCV) is a global public health concern, particularly in the prison setting where prevalence is substantially higher than in the general population. Direct‐acting antivirals have changed the treatment landscape, allowing for treatment scale‐up efforts potentially sufficient to achieve prevention of onward transmission (treatment‐as‐prevention). The Surveillance and Treatment of Prisoners with hepatitis C (SToP‐C) study was the first trial to examine the efficacy of HCV treatment‐as‐prevention in the prison setting. Social capital is a social resource which has been found to influence health outcomes. This qualitative study sought to understand the role of social capital within an HCV treatment‐as‐prevention trial in the prison setting. Design: Semi‐structured in‐depth interviews were undertaken with participants recruited from the SToP‐C study following HCV treatment completion (with cure). Setting: Three male correctional centres in New South Wales, Australia (including two maximum‐security and one minimum‐security). Participants: Twenty‐three men in prison participated in semi‐structured interviews. Measurements: Thematic analysis of transcripts was completed using a social capital framework, which enabled exploration of the ways in which bonding, bridging and linking social capital promoted or inhibited HCV treatment uptake within a treatment‐as‐prevention trial. Findings: Social capital fostered HCV treatment uptake within an HCV treatment‐as‐prevention trial in the prison setting. Bonding social capital encouraged treatment uptake and alleviated concerns of side effects, bridging social capital supported prison‐wide treatment uptake, and linking social capital fostered trust in study personnel (including nurses and correctional officers), thereby enhancing treatment engagement. Conclusions: Social capital, including bonding, bridging and linking, can play an important role in hepatitis C treatment‐as‐prevention efforts within the male prison setting.